Cognitive profiles of patients with mild cognitive impairment due to Alzheimer's versus Parkinson's disease defined using a base rate approach: Implications for neuropsychological assessments. Issue 1 (14th September 2021) - Ophey, Anja; Wolfsgruber, Steffen; Roeske, Sandra; Polcher, Alexandra; Spottke, Annika; Frölich, Lutz; Hüll, Michael; Jessen, Frank; Kornhuber, Johannes; Maier, Wolfgang; Peters, Oliver; Ramirez, Alfredo; et al.
Abstract: Introduction: Large studies on cognitive profiles of patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD‐MCI) compared to Parkinson's disease (PD‐MCI) are rare. Methods: Data from two multicenter cohort studies in AD and PD were merged using a unified base rate approach for the MCI diagnosis. Cognitive profiles were compared using scores derived from the Consortium to Establish a Registry for Alzheimer's Disease battery. Results: Patients with AD‐MCI showed lower standardized scores on all memory test scores and a language test. Patients with PD‐MCI showed lower standardized scores in a set‐shifting measure as an executive task. A cross‐validated logistic regression with test scores as predictors was able to classify 72% of patients correctly to AD‐MCI versus PD‐MCI. Discussion: The applied test battery successfully discriminated between AD‐MCI and PD‐MCI. Neuropsychological test batteries in clinical practice should always include a broad spectrum of cognitive domains to capture any cognitive changes.